Professional activity and social inclusion of people aged 50+ as the priority objectives for regional social policy - Przywojska, Justyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The reflections undertaken in this article concern the issue of strategic planning of regional social policy related to older people. Due to the changes to the political system in Poland, initiated in 1989 and continued in 1999, local and regional authorities have been transformed into a kind of independent organizations pursuing their own policies based on long-term action plans – strategies. The aim of this article is to present the measures for supporting the opportunities and improve the quality of life of people aged 50+, programmed in voivodeship strategies relating to wider social policy issues.